The “What” of Athletes’ Goal Pursuit and Its Relationships to Goal-Related Processes and Well- and Ill-Being - Natalia Martínez-González; Francisco L. Atienza; Joan L. Duda; Isabel Balaguer (Behavioral Sciences)
Goal Contents Theory (GCT) postulates that the goals people pursue not only direct their perceptions of and behaviors relevant to goal pursuit, but also hold implications for their well- and ill-being. Extending past sport work grounded in this theory, this study explored athletes’ self-generated goals and examined whether these goals were differentially aligned with goal-related processes and well- and ill-being. A total of 414 university team athletes (206 women and 208 men) completed a questionnaire at the beginning of the sport season. The results showed that intrinsic goals, assessed in an open-ended format, were more heterogeneous in terms of content, and more common among athletes than extrinsic goals. In addition, women reported more intrinsic goals and fewer extrinsic goals than men. MANCOVA revealed that athletes who pursued extrinsic goals reported significantly lower self-efficacy and greater perceptions of goal difficulty than athletes with intrinsic goals. No differences in goal motives and well- and ill-being indicators emerged. Finally, two models were tested that illustrate how goal content is related to self-efficacy for goal attainment, goal motives, and well- and ill-being. Overall, the findings were largely congruent with GCT and indicate that the quality of athletes’ goal-related processes and their well- and ill-being vary as a function of whether they are pursuing intrinsic or extrinsic goals.